Importance of the fluid-particle drag model in predicting segregation in bidisperse gas-solid flow. (November 2016) - Mehrabadi, Mohammad; Tenneti, Sudheer; Subramaniam, Shankar
Highlights: Presence of a carrier flow in a bidisperse suspension gives rise to the development of a mean slip velocity between the two particle size classes. Current closure models for gas-particle drag and particle drag forces are not able to accurately predict this mean slip velocity. Improvements in predicting the slip velocity between the two particle size classes is achieved by proposing a more accurate gas-particle drag model based on particle-resolved DNS results of fixed bidisperse assemblies. Abstract: The slip velocity between particle size classes in a homogeneous bidisperse gas-solid flow is quantified using particle-resolved direct numerical simulation (PR-DNS). This slip velocity is the key characteristic of size segregation in industrial devices. The ability of current gas-particle drag models to predict this slip velocity is examined by simultaneously solving the mean momentum equations for the gas phase and dispersed phases. PR-DNS of fixed particle assemblies is then used to validate and improve the bidisperse gas-particle drag model. The drag model inferred from bidisperse fixed beds is compared with the drag force measured from PR-DNS of freely evolving bidisperse suspensions. The ability of this new model to predict the slip velocity between particle size classes in a bidisperse gas-solid flow is also examined.